Language, school and society: The status of German in Hungarian public education - Markovics, Katalin (Central European Journal of Educational Research, 2025)
Bibliography of the reviewed book: Sebestyén, K. (2023). Kik és miért tanulnak németet az érettségit adó képzésekben? [Who and why do the study German in the programs with secondary school leaving exam?]. Debrecen University Press.